2020
DOI: 10.1038/s43246-020-0023-4
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic organic interface for neuronal stimulation in the near-infrared

Abstract: Organic materials, such as conjugated polymers, are attractive building blocks for bioelectronic interfaces. In particular, organic semiconductors show excellent performance in lightmediated excitation and silencing of neuronal cells and tissues. However, the main challenges of these organic photovoltaic interfaces compared to inorganic prostheses are the limited adhesion of conjugated polymers in aqueous environments and the exploitation of materials responsive in the visible spectrum. Here, we show a photovo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 60 publications
0
39
0
Order By: Relevance
“…For the intensity of 0.57 mW mm −2 , type I and type II biointerfaces produce -65 ± 7 mV and 175 ± 13 mV (Mean ± SD, for N = 8) photovoltages under 10 ms pulse, respectively. These numbers are promising for potential photostimulation applications considering the reported photovoltage values in a previous QD-based study that can evoke neural activity (Bareket et al, 2014), and also previous organic semiconductor-based biointerface studies that reported similar or lower photovoltage values and still effectively stimulate neurons (Gautam et al, 2014;Ciocca et al, 2020;Leccardi et al, 2020).…”
Section: Photoelectrical Performance Of Biointerfacesmentioning
confidence: 69%
“…For the intensity of 0.57 mW mm −2 , type I and type II biointerfaces produce -65 ± 7 mV and 175 ± 13 mV (Mean ± SD, for N = 8) photovoltages under 10 ms pulse, respectively. These numbers are promising for potential photostimulation applications considering the reported photovoltage values in a previous QD-based study that can evoke neural activity (Bareket et al, 2014), and also previous organic semiconductor-based biointerface studies that reported similar or lower photovoltage values and still effectively stimulate neurons (Gautam et al, 2014;Ciocca et al, 2020;Leccardi et al, 2020).…”
Section: Photoelectrical Performance Of Biointerfacesmentioning
confidence: 69%
“…[ 240 ] Either conductive polymers [ 241–243 ] or graphene [ 244 ] arrays are used to enhance this conversion, and enable photovoltaic subretinal implants. [ 245,246 ] Electrodes can be designed as pillars, and in a honeycomb lattice, to improve the electrode resolution and more effectively stimulate the retinal neurons. [ 247–249 ] Other models of electrode structures may further improve these interfaces.…”
Section: Surface Electrode Arrays For the Central And Peripheral Nerv...mentioning
confidence: 99%
“…[ 247–249 ] Other models of electrode structures may further improve these interfaces. [ 250 ] While some retinal surface arrays have a comparable number of electrodes to the implants used for the brain or spinal cord (between 16 and 32 electrodes), most have more than a thousand [ 251,252 ] and as many as 10 500 electrodes [ 245 ] in order to recreate as high resolution of an image as possible.…”
Section: Surface Electrode Arrays For the Central And Peripheral Nerv...mentioning
confidence: 99%
“…These polymeric hydrogel nanomaterials are often used as supportive scaffolds which satisfy the biochemical and biophysical microenvironment needs for optimal neural functioning while allowing for electrical stimulation to control the activities of the neuron ( Farokhi et al., 2021 ). Organic semiconductors can also inhibit or stimulate action potentials in neurons through light excitation ( Leccardi et al., 2020 ). For example, optical controlling of conjugated polymer films interfaced on neurons can promote neuronal silencing ( Feyen et al., 2016 ).…”
Section: Mechanisms Of Neuronal Modulationmentioning
confidence: 99%